2015
DOI: 10.2147/ijn.s72330
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic nanolayers: structure, preparation, and biomedical applications

Abstract: Hydrotalcite-like compounds are two-dimensional inorganic nanolayers also known as clay minerals or anionic clays or layered double hydroxides/layered hydroxy salts, and have emerged as a single type of material with numerous biomedical applications, such as drug delivery, gene delivery, cosmetics, and biosensing. Inorganic nanolayers are promising materials due to their fascinating properties, such as ease of preparation, ability to intercalate different type of anions (inorganic, organic, biomolecules, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 153 publications
(205 reference statements)
1
24
0
Order By: Relevance
“…The correlation coefficients (R 2 ) of the three models were deduced from the graphs and are presented in Table 1 along with rate constant (K), percentage saturation (%) and t 1∕2 (min) of the sample in both pHs. The drug kinetic release data like several other reported kinetic release data of some drugs from different nano-carriers, was observed to have matched best to the pseudo-second order (Bullo and Hussein 2015;Bullo et al 2013;Dorniani et al 2012Dorniani et al , 2014Tan et al 2014), with R 2 value of 0.982 ( Fig. 4) against 0.560 and 0.695 for pseudo-first order and parabolic diffusion, respectively, in pH 4.8.…”
Section: Kinetic Studies Of the Drug Releasesupporting
confidence: 71%
See 2 more Smart Citations
“…The correlation coefficients (R 2 ) of the three models were deduced from the graphs and are presented in Table 1 along with rate constant (K), percentage saturation (%) and t 1∕2 (min) of the sample in both pHs. The drug kinetic release data like several other reported kinetic release data of some drugs from different nano-carriers, was observed to have matched best to the pseudo-second order (Bullo and Hussein 2015;Bullo et al 2013;Dorniani et al 2012Dorniani et al , 2014Tan et al 2014), with R 2 value of 0.982 ( Fig. 4) against 0.560 and 0.695 for pseudo-first order and parabolic diffusion, respectively, in pH 4.8.…”
Section: Kinetic Studies Of the Drug Releasesupporting
confidence: 71%
“…The profiles were obtained by matching the absorbances from the release, which are expressed in percentage against time of release; the release in both pHs varies at both time of release as well as the percentage of release. Although it is quite common and expected for guest molecules intercalated within LDH gallery to release more in the acidic medium than in the alkaline medium (Bullo and Hussein 2015;Usman et al 2017a, b), as observed in this case (98% at pH 4.8 and 20% at pH 7.4), it is, however, uncommon for the intercalated guest to vary in period of release at different pHs. As can be observed in Fig.…”
Section: In Vitro Drug Release Studymentioning
confidence: 55%
See 1 more Smart Citation
“…Zn/Al-layered double hydroxide (LDH) is one of the candidates capable of simultaneously intercalating and adsorbing theranostic agents due to their exchangeable interlayer anions. LDH is one of the group of two-dimensional layered structures materials [ 13 ] and has the general formula of [ (OH) 2 ] x + [A n − ] x / n · m H 2 O] [ 14 ], where divalent and trivalent metal cations are represented by M 2+ and M 3+ , respectively, and interlayer exchangeable anions are represented by [A n − ], and water as x / n [ 8 , 15 , 16 , 17 ]. Gallic acid is the therapeutic agent employed in this research; it is a naturally occurring polyhydroxyl phenolic compound, often found in different kinds of fruits.…”
Section: Introductionmentioning
confidence: 99%
“…This fraction determines the electrostatic charge density in the layers, thus influencing the size of the interlayer space and a variety of physicochemical properties such as adhesion, reactivity, ion-exchange capacity, and rotation of chemical species into the interlayer space and on the surface [7]. More details related to the structure of LDH can be found in some published revisions [9,10].…”
Section: Layered Double Hydroxidesmentioning
confidence: 99%